Comparing effects of school inspections in Sweden and Austria - Kemethofer, David; Gustafsson, Jan-Eric; Altrichter, Herbert (Educational Assessment, Evaluation and Accountability, 2017)
In recent years, school inspections have been newly introduced or adapted to the evidence-based governance logic in many European countries. So far, empirical research on the impact of school inspections has produced inconclusive results. Methodologically, it has mainly focussed on analysis of a national inspection model and used cross-sectional data. In the following paper, we investigate the effects of school inspections in a comparative and longitudinal perspective in Sweden and Austria (province of Styria). In these countries, inspections follow different governance approaches. While Austria represents a low-stakes system which does not link consequences for schools to inspection results, sanctions and even financial penalties are potential consequences of Swedish inspections. To discuss the effects of inspections, we asked principals in three consecutive years about the impact of inspections. Our results indicate that school inspections in Austria and Sweden do have a small to medium impact on school improvement and school effectiveness.
Keywords: Comparative research; Inspection systems; School effectiveness; School inspection; school improvement